Impact of deficit irrigation on water use efficiency and carbon isotope composition (δ13C) of field-grown grapevines under Mediterranean climate - Souza, Cláudia R. de (2012)
The objective of this study was to evaluate the effect of deficit irrigation on intrinsic water use efficiency (A/gs) and carbon isotope composition (δ 13C) of two grapevine cultivars (Moscatel and Castelão), growing in a commercial vineyard in SW Portugal. The study was done in two consecutive years (2001 and 2002). The treatments were full irrigation (FI), corresponding to 100% of crop evapotranspiration (ETc), rain-fed (no irrigation, NI), and two types of deficit irrigation (50% ETc): (i) by supplying the water either to one side of the root system or to the other, which is partial rootzone drying (PRD), or (ii) dividing the same amount of water by the two sides of the root system, the normal deficit irrigation (DI). The water supplied to the PRD treatment alternated sides approximately every 15 d. The values of predawn leaf water potential (ψpd) and the cumulative integral of ψpd (Sψ) during the season were lower in 2001 than in the 2002 growing season. Whereas differences in Wpd and SW between PRD and DI were not significantly different in 2001, in 2002 (a dryer year) both cultivars showed lower values of SW in the PRD treatment as compared with the DI treatment. This suggests that partial rootzone drying may have a positive effect on water use under dryer conditions, either as a result of better stomatal control and/or reduced vigour. The effects of the water treatments on δ13C were more pronounced in whole grape berries and pulp than in leaves. The δ13C of pulp showed the best correlation with intrinsic water use efficiency (A/gs) as well as with Sψ. In spite of the better water status observed in PRD compared with DI in the two cultivars in 2002, no statistical differences between the two treatments were observed in A/gs and δ13C. On the other hand, they showed a higher δ13C compared with FI. In conclusion, it is apparent that the response to deficit irrigation varies with the environmental conditions of the particular year, the driest conditions exacerbating the differences among treatments. The highest values of d13C found in the pulp of NI vines in Castela˜o compared with Moscatel suggest different sensitivities to water deficits in the two cultivars, as was empirically observed.